Advances in extracellular vesicle (EV) biomarkers for precision diagnosis and therapeutic in colorectal cancer - Zhang, Li; Shen, Hui; Zhang, Nenghua (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is the second most common cause of cancer-related mortality worldwide and one of the most frequently diagnosed malignancies. Conventional CRC screening techniques—such as colonoscopy and pathologic biopsy—are invasive procedures that often cause patient discomfort and carry risks of complications. Recently, extracellular vesicles (EVs) have gained prominence as a promising area of investigation in oncology research. EVs are nanoscale, membrane-bound particles secreted by cells, which encapsulate and protect nucleic acids, proteins, and other biomolecules within their phospholipid bilayer structure. This protective characteristic renders EVs highly suitable as non-invasive diagnostic biomarkers for CRC, as well as efficient nanocarriers for targeted drug delivery vehicles. This review examines the functional roles, regulation mechanisms, and translational potential of EVs in CRC. Specifically, it investigates how EVs drive CRC pathogenesis through tumour microenvironment remodeling, immune suppression, and metastatic dissemination. Additionally, the review examines relevant methodologies for EV sample collection, isolation, and detection, which are critical for translating EV-based diagnostics and therapeutics into clinical practice. In conclusion, EVs represent a transformative approach in CRC research, offering non-invasive diagnostic tools and innovative therapeutic strategies. By integrating advanced methodologies and elucidating the regulatory mechanisms of EVs, this review provides valuable insights for advancing precision medicine in CRC, ultimately improving patient outcomes and reducing the global burden of this disease.